IPhone 12 MagSafe technology and cardiac implantable devices: Assessment of the actual risk. Issue 3 (11th February 2022) - Censi, Federica; Mattei, Eugenio; Onder, Graziano; Calcagnini, Giovanni
Abstract: Background: Pacemaker (PM) and implantable cardioverter defibrillators (ICD) are equipped with a magnetic sensor activated by external application of magnets to easily manage some functions of these devices. If activated inadvertently or outside a controlled environment and without the supervision of clinical personnel, this magnetic mode introduces a potential risk. In reality, the possibility of a static magnetic field affecting a PM or ICD is remote. However, the presence of the magnet in the iPhone 12 made the possibility of inadvertently activating the magnetic switch of PM and ICD less remote. Objective: This study investigates the effects of magnetic interference of the iPhone 12 on a large set of cardiac implantable devices representative of the current market and proposes adequate rules of conduct. Methods: We investigated the risk of the magnetic interference of the iPhone 12 and its MagSafe accessories on a comprehensive set of PMs and ICDs, including the subcutaneous ICD. For the first time, the magnetic interference phenomena were correlated with the magnetic field levels measured all around iPhone 12. Results: We discovered that the magnets inside iPhone 12 trigger the magnetic mode in the 12 tested devices up to a distance of 1 cm. Conclusions: Considering the implications related to the activation of the magnetic switch, to date, it is advisable to follow Apple's indications relating to the safety distance of 15 cm, which is widely compatible with the results obtained from this paper and in line with the indications provided by the implantable cardiac device manufacturers.